BUILDING SOLUTIONS WITH THE USAGE OF DEFECATE - WASTE OF SUGAR INDUSTRY - Шульгин, В. В.; Гукасян, О. М.; Дмитренко, Р. Н.; Безверхий, И. В.; Скворцов, Д. В. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article presents the results of defecate,waste of sugar industry. The experimental research and data on the effect of defecate on the strength of brands solution M 50 –M 300 are produced. The effect of defecate consumption on the water-holding capacity and delamination of solution is studied. Keywords:building mortar, defecate, strength, water-holding capacity, delamination.